Mineral and Bone Disorders After Kidney Transplantation - Vangala, Chandan; Pan, Jenny; Cotton, Ronald T.; Ramanathan, Venkat (Frontiers in Medicine, 2018)
The risk of mineral and bone disorders among patients with chronic kidney disease is substantially elevated, owing largely to alterations in calcium, phosphorus, vitamin D, parathyroid hormone, and fibroblast growth factor 23. The interwoven relationship among these minerals and hormones results in maladaptive responses that are differentially affected by the process of kidney transplantation. Interpretation of conventional labs, imaging, and other fracture risk assessment tools are not standardized in the post-transplant setting. Post-transplant bone disease is not uniformly improved and considerable variation exists in monitoring and treatment practices. A spectrum of abnormalities such as hypophosphatemia, hypercalcemia, hyperparathyroidism, osteomalacia, osteopenia, and osteoporosis are commonly encountered in the post-transplant period. Thus, reducing fracture risk and other bone-related complications requires recognition of these abnormalities along with the risk incurred by concomitant immunosuppression use. As kidney transplant recipients continue to age, the drivers of bone disease vary throughout the post-transplant period among persistent hyperparathyroidism, de novo hyperparathyroidism, and osteoporosis. The use of anti-resorptive therapies require understanding of different options and the clinical scenarios that warrant their use. With limited studies underscoring clinical events such as fractures, expert understanding of MBD physiology and surrogate marker interpretation is needed to determine ideal and individualized therapy.